Preparation and characterization of Lithium-stabilized Colloidal Silica as a silicate densifier for concrete surface treatment - Nguyen, Hoang Thien Khoi; Nguyen, Ngoc Tri Huynh; Huynh, Ngoc Minh; Nguyen, Khanh Son (Vietnam Journal of Science and Technology, 2024)
Enhancing the durability of concrete by safeguarding it against cracking and environmental deterioration is paramount. While silicate-based densifiers have been instrumental in shielding concrete surfaces from wear and environmental factors, the surging popularity of lithium silicate solutions faces a significant impediment due to the high cost of lithium, mainly attributed to its predominant use in manufacturing lithium batteries. To address this substantial challenge, an intriguing approach involves blending lithium silicate with colloidal silica, potentially offering a cost-effective and efficient solution for concrete surface treatment. This study delves into the feasibility of utilizing lithium-stabilized colloidal silica as a silicate densifier, focusing on their preparation, characterization, and efficacy in lab-scale applications. The results demonstrate that lithium-stabilized colloidal silica can heighten surface hardness while concurrently reducing porosity. However, it is worth noting that this approach presents particular challenges, particularly regarding preparation and water resistance, when compared to surfaces treated solely with lithium silicate. Addressing these hurdles holds promise for optimizing and enhancing lithium-stabilized colloidal silica and advancing the concrete surface treatment field in future research endeavours.